Implementation of Public Service Innovations to Prevent the Spread of the Covid 19 Virus (Descriptive Study of Innovation in the Ketanmu Postal Service at the Mojokerto Regency Population and Civil Registration Service) - Wuryani*, Wuryani; Orbaningsih, Dwi; Budi Wahyono, Gendut (Universitas Syiah Kuala, 2023)
Pos Ketanmu is an abbreviation of the Online Service of the Unmet Population System. Service innovations that were born during the Covid-19 virus phenomenon. Which is to prevent the occurrence of crowds during the processing of population documents. This Ketanmu Postal service innovation program has touched the important needs of the people of Mojokerto Regency, namely the service of Population Documents in the form of KK, KTPel, Birth Certificates, Moving/coming, etc. which are easily accessible by all social strata of society. This study aims to analyze the implementation and the inhibiting factors in the implementation of public service innovations at the Ketanmu Post Office at the Mojokerto Regency Population and Civil Registration Office. With this innovation, residents do not need to come to the Population and Civil Registration Office, but just stay at home. Residents who want to take care of residence documents simply register via whatsapp to the number provided by the District Dispendukcapil. Mojokerto. This research is descriptive through case studies. The type/type of this research is a descriptive study. Data collection is done through observation, interviews, and documentation. Data were analyzed using a qualitative approach. The results of the research from the implementation of Adminduk service innovations through the Ketanmu Post program indicate that the implementation of Adminduk service innovations through the Ketanmu Post program is still not fully implemented in accordance with the criteria for public service innovation. The presence of inhibiting factors that affect the process of implementing the program makes the implementation of this program still limited by people who understand WhatsApp, socialization is not evenly distributed, human resources are less capable, and there is still a lack of participation levels that still do not involve many parties in it. Also, this program is still questionable because the innovation of Pos Ketanmu has not been based on regional regulations